Analysis of the Impact of Monetary Policy Tools on the Gross Domestic Product in Iraq for the Period (2005-2020) - Rawaa Yahya Khalaf; Elaf Muhsin Ali; Zahid. K. Badan (HM Journals, 2023)
Monetary policy in Iraq, as it is in other countries, aims to achieve balance and economic stability, and to control the general level of prices, in addition to other goals that seek to be reached by the monetary authority. From the rise in crude oil prices in global markets, and it was found that there is a joint integration between the variables of the model, which means that the variables included in the model have the ability to correct structural imbalances and the possibility of overcoming obstacles facing the Iraqi economy, that monetary policy plays a simple and traditional role in its impact on the whole One of the important variables, so the researchers recommended developing a strategy that makes the extractive sector the locomotive of growth in the Iraqi economy and contributes to creating forward and backward links between the economic sectors and achieves economic development in Iraq